Enterovaginal or Vesicovaginal Fistula Control Using a Silicone Cup. Issue 6 (December 2016) - Russell, Katie W.; Robinson, Ryan E.; Mone, Mary C.; Scaife, Courtney L.
Abstract : BACKGROUND: An enterovaginal or vesicovaginal fistula is a complication resulting in vaginal discharge of succus, urine, or stool that can lead to significant complications. For low-volume fistulae, tampons or pads may be used. With high-volume fistulae, frequent product change can be painful and unpredictable in terms of efficacy. The psychologic distress is profound. Surgery may not be an option, making symptom control the priority. INSTRUMENT: We report the use of a reusable menstrual silicone vaginal cup placed to divert and contain drainage. EXPERIENCE: The menstrual cup provided significant symptom relief. Drainage is immediately diverted from tissue, unlike with tampon or pad use, which involves longer contact periods with caustic fluids. A system was created by adapting the end of the cup by adding silastic tubing and an external leg bag to provide long-term drainage control. CONCLUSION: Improvement in quality of life is of primary importance when dealing with fistula drainage. This simple and inexpensive device should be considered in those cases in which the drainage can be diverted as a viable option, especially in those who are symptomatic and awaiting surgical repair or in those for whom surgery cannot be performed. Abstract : Use of a vaginal silicone menstrual cup to control drainage from enterovaginal or vesicovaginal fistulae can significantly reduce symptomology and improve quality of life.